TO STUDY THE EFFECT OF THE TRADITIONAL MEDICINE REMEDY "BO THAN SINH TINH THANG" ON THE CAVERNOSUM PRESSURE OF WHITE MALE RATS (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluation of the effect of the traditional medicine remedy «Bo than sinh tinh thang» onthe cavernosum pressure of male Wistar rats.Method: To study on 40 male Wistar rats 24-week-old oral «Bo than sinh tinh thang» remedyextract only once, after anesthesia and measured ICP (intracavernous pressure) before taking thedrug. Measurement of ICP, arterial blood pressure by powerlab system before and after stimulatingcavernous nerves at the time before and after taking drugs 15 minutes, 30 minutes, 45 minutes.Results: “Bo than sinh tinh thang” increased basal ICP at 30 minutes and 45 minutes after takingdrugs (p
Keywords: Bo than sinh tinh thang, intracavernous pressure, male Wistar rats.